Hypouricemic effect of Grifola frondosa on hyperuricemic mice and virtual screening of bioactives by 3D QSAR pharmacophore modeling. (January 2018) - Yong, Tianqiao; Xie, Yizhen; Chen, Shaodan; Chen, Diling; Su, Jiyan; Jiao, Chunwei; Hu, Huiping; Xiao, Chun
Highlights: Extracts of G. frondosa produced significant decreases in serum uric acid levels. Have no negative impacts on liver, renal and spleen functions. 3D-QSAR pharmacophore model Hypo1 developed and validated in high quality. Four compounds were hit and mapped well to Hypo1. Abstract: Grifola frondosa (GF) has been exploited as herb medicine for metabolic diseases and also as tasty food in Asia. Water (GFW) and ethanol (GFE) extracts produced remarkable hypouricemic effects, thereby decreasing the levels of serum uric acid from 240 μmol/L (hyperuricemia control, P  < .01) to 170, 169, and 153 μmol/L for GFW at doses of 30, 60, and 120 mg/kg and to 169, 168, and 156 μmol/L for GFE at 50, 100, and 200 mg/kg correspondingly, which were similar to the normal control (159 μmol/L). ELISA analysis demonstrated the inhibitory effects of GFW and GFE on URAT1 protein rather than xanthine oxidase (XOD). The 3D-QSAR pharmacophore model for URAT1 was established successfully. Four compounds were identified and mapped adequately, deserving further study. Taken together, G. frondosa is a promising candidate for the development of functional foods.